The role of wall shear stress in the parent artery as an independent variable in the formation status of anterior communicating artery aneurysms - Zhang, Xin; Yao, Zhi-Qiang; Karuna, Tamrakar; He, Xu-Ying; Wang, Xue-Min; Li, Xi-Feng; Liu, Wen-Chao; Li, Ran; Guo, Shen-Quan; Chen, Yun-Chang; Li, Gan-Cheng; Duan, Chuan-Zhi (European radiology, 2019)
Objectives The study aimed to determine which hemodynamic parameters independently characterize anterior communicating artery (AcomA) aneurysm formation and explore the threshold of wall shear stress (WSS) of the parent artery to better illustrate the correlation between the magnitude of WSS and AcomA aneurysm formation. Methods Eighty-one patients with AcomA aneurysms and 118 patients without intracranial aneurysms (control population), as confirmed by digital subtraction angiography (DSA) from January 2014 to May 2017, were included in this cross-sectional study. Three-dimensional-DSA was performed to evaluate the morphologic characteristics of AcomA aneurysms. Local hemodynamic parameters were obtained using transcranial color-coded duplex (TCCD). Multivariate logistic regression and a two-piecewise linear regression model were used to determine which hemodynamic parameters are independent predictors of AcomA aneurysm formation and identify the threshold effect of WSS of the parent artery with respect to AcomA aneurysm formation. Results Univariate analyses showed that the WSS ( p < 0.0001), angle between the A1 and A2 segments of the anterior cerebral artery (ACA) ( p < 0.001), hypertension (grade II) ( p = 0.007), fasting blood glucose (FBG; > 6.0 mmol/L) ( p = 0.005), and dominant A1 ( p < 0.001) were the significant parameters. Multivariate analyses showed a significant association between WSS of the parent artery and AcomA aneurysm formation ( p = 0.0001). WSS of the parent artery (7.8-12.3 dyne/cm 2 ) had a significant association between WSS and aneurysm formation (HR 2.0, 95% CI 1.3-2.8, p < 0.001). Conclusions WSS ranging between 7.8 and 12.3 dyne/cm 2 independently characterizes AcomA aneurysm formation. With each additional unit of WSS, there was a one-fold increase in the risk of AcomA aneurysm formation. Key Points • Multivariate analyses and a two-piecewise linear regression model were used to evaluate the risk factors for AcomA aneurysm formation and the threshold effect of WSS on AcomA aneurysm formation. • WSS ranging between 7.8 and 12.3 dyne/cm 2 was shown to be a reliable hemodynamic parameter in the formation of AcomA aneurysms. The probability of AcomA aneurysm formation increased one-fold for each additional unit of WSS. • An ultrasound-based TCCD technique is a simple and accessible noninvasive method for detecting WSS in vivo; thus, it can be applied as a screening tool for evaluating the probability of aneurysm formation in primary care facilities and community hospitals because of the relatively low resource intensity.